Portability | portable (depends on ghc) |
---|---|

Stability | provisional |

Maintainer | bastiaan.heeren@ou.nl |

Safe Haskell | Safe-Inferred |

Datatype for representing a derivation (parameterized both in the terms and the steps)

- data Derivation s a
- emptyDerivation :: a -> Derivation s a
- prepend :: (a, s) -> Derivation s a -> Derivation s a
- extend :: Derivation s a -> (s, a) -> Derivation s a
- isEmpty :: Derivation s a -> Bool
- derivationLength :: Derivation s a -> Int
- terms :: Derivation s a -> [a]
- steps :: Derivation s a -> [s]
- triples :: Derivation s a -> [(a, s, a)]
- firstTerm :: Derivation s a -> a
- lastTerm :: Derivation s a -> a
- lastStep :: Derivation s a -> Maybe s
- withoutLast :: Derivation s a -> Derivation s a
- updateSteps :: (a -> s -> a -> t) -> Derivation s a -> Derivation t a
- derivationM :: Monad m => (s -> m ()) -> (a -> m ()) -> Derivation s a -> m ()

# Data type

data Derivation s a Source

BiFunctor Derivation | |

(Typed a t1, Typed a t2) => Typed a (Derivation t1 t2) | |

Functor (Derivation s) | |

(Show s, Show a) => Show (Derivation s a) |

# Constructing a derivation

emptyDerivation :: a -> Derivation s aSource

prepend :: (a, s) -> Derivation s a -> Derivation s aSource

extend :: Derivation s a -> (s, a) -> Derivation s aSource

# Querying a derivation

isEmpty :: Derivation s a -> BoolSource

Tests whether the derivation is empty

derivationLength :: Derivation s a -> IntSource

Returns the number of steps in a derivation

terms :: Derivation s a -> [a]Source

All terms in a derivation

steps :: Derivation s a -> [s]Source

All steps in a derivation

triples :: Derivation s a -> [(a, s, a)]Source

The triples of a derivation, consisting of the before term, the step, and the after term.

firstTerm :: Derivation s a -> aSource

lastTerm :: Derivation s a -> aSource

lastStep :: Derivation s a -> Maybe sSource

withoutLast :: Derivation s a -> Derivation s aSource

updateSteps :: (a -> s -> a -> t) -> Derivation s a -> Derivation t aSource

derivationM :: Monad m => (s -> m ()) -> (a -> m ()) -> Derivation s a -> m ()Source

Apply a monadic function to each term, and to each step